2014
DOI: 10.3892/ijo.2014.2675
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the serum proteome profile during the development of ovarian cancer

Abstract: Abstract. Ovarian cancer causes more deaths than any other malignant tumor of the female reproductive system. This is because the condition usually goes undetected until the late stages. The purpose of the present study is to identify alterations in the serum proteome profile during the development of ovarian cancer and to provide an experimental basis for discovering new and valuable serum biomarkers for the early detection of ovarian carcinoma. Surface-enhanced laser desorption/ionization-time of flight (SEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Hence, our hope is that additional studies will be performed adhering to the study design principles described herein to discover novel serum protein signatures to improve not only the early detection of ovarian cancer, but also the guidance on ovarian cancer therapy. Biomarker research is now focusing on the discovery of different biomarkers either in serum or plasma expressed in different stages and different subtypes of the disease [ 17 , 196 , 197 , 198 ].…”
Section: Clinical Serum/plasma Proteomics and Molecular Signaturesmentioning
confidence: 99%
“…Hence, our hope is that additional studies will be performed adhering to the study design principles described herein to discover novel serum protein signatures to improve not only the early detection of ovarian cancer, but also the guidance on ovarian cancer therapy. Biomarker research is now focusing on the discovery of different biomarkers either in serum or plasma expressed in different stages and different subtypes of the disease [ 17 , 196 , 197 , 198 ].…”
Section: Clinical Serum/plasma Proteomics and Molecular Signaturesmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a potent mediator of angiogenesis that induces the formation of novel blood vessels, and growth and metastasis of cancers. Several researches have revealed that VEGF plays an important role in promoting endothelial cell proliferation and migration, and induces a direct effect on cancer proliferation and invasiveness (Awazu et al 2013;Hu et al 2013;Sun et al 2014). It has been reported that TBC domain containing proteins also participate in cancer proliferation and angiogenesis via VEGF (Kim et al 2003;Ji et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The growth and spread of tumors depends on the formation of an adequate vascular support and amoeboid mode of tumor cell invasion (9). Furthermore, several studies have indicated that VEGF serves a role in promoting endothelial cell proliferation and migration, and induces a direct effect on cell proliferation and invasiveness (3,10,11). Previous studies have indicated that suppressing the expression or activity VEGF in ovarian cancer cells may represent a potential anticancer therapy (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%